Guest Editorial Vol12 no2 - Janine Bolger (Scottish Journal of Residential Child Care, 2013)
Increasing interest in social pedagogy throughout Scotland appears to be reflected, strategically, through the emergence of training by organisations such as ThemPra, the evaluation of training programmes (Milligan 2009, and see Evelyn Vrouwenfelder's article in this issue), through bi-annual meetings of stakeholders and practitioners via the social pedagogy Development Network, through study visits by agency staff to European projects (ThemPra Mobility Project 2012) and by the increasing number of related articles and books being published.